Supporting Students through a Recommendation System for Knowledge Acquisition in MOOCs Ecosystems - Campos, Rodrigo; Santos, Rodrigo Pereira dos; Oliveira, Jonice (Anais Estendidos do Congresso Brasileiro de Informática na Educação (CBIE), 2020)
With the growth of MOOCs (Massive Open Online Courses), students face difficulties in choosing more suitable courses for a knowledge demand. Some recommendation systems have proposed solutions, but not exploring the student's prior knowledge. In this context, this work contributes to identifying and reducing the students' knowledge gap in MOOCs. To do so, we model and analyze the MOOCs ecosystems and propose a solution for recommending parts of courses to students, exploring the software ecosystem approach in the educational domain. After evaluating our solution based on three experiments, we observed that our recommendations present new content to fill users? knowledge gaps, being accurate, useful, and reliable.